2011
DOI: 10.1021/jo200648h
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Asymmetry in Concerted Reactions: Solvents Effect on a Diels–Alder Cycloaddition

Abstract: We propose the notion that if asymmetry characterizes a concerted reaction, a quantitative treatment in terms of continuous symmetry can bridge the gap between the Woodward-Hoffmann (WH) rules, originally formulated for symmetry-idealized unsubstituted reactants, and the fact that these rules hold for a much wider scope of reactions. Instead of focusing on symmetry conservation along the minimum energy path, we suggest that the distortion with respect to the original expected symmetry must attain a certain min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…In continuation of our previous study, [4] here too we suggest the notion that when perfect symmetry is inherently impossible in a concerted reaction, the continuous symmetry measure attains a certain minimal value, not necessarily zero. In this paper, we have demonstrated this idea on a large set of asymmetrically substituted DA reactions in seven different solvents and in the gas phase.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…In continuation of our previous study, [4] here too we suggest the notion that when perfect symmetry is inherently impossible in a concerted reaction, the continuous symmetry measure attains a certain minimal value, not necessarily zero. In this paper, we have demonstrated this idea on a large set of asymmetrically substituted DA reactions in seven different solvents and in the gas phase.…”
Section: Resultssupporting
confidence: 70%
“…In a recent publication, [4] we suggested that the distorted symmetry of the transition state (TS) of the DA reaction of (E,E)-1,4-dimethoxy-1,3-butadiene with tetracyanoethylene does retain some of the original symmetry, in which the word "some" relates to the quantification of the degree of symmetry content as calculated by the continuous symmetry measures (CSM) method. [5] We briefly recall that the CSM approach extends the binary language of symmetry into a continuous scale while combining all of the geometrical parameters of a molecular structure into a single global parameter that describes the distance of that structure from the desirable symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Combining with taking the limited water solubility of DB and EM into account, it is the result of the reaction largely taking place at the interface, where it was much faster than that in an organic solvent. The reason is the excellent solubilization, particular orientation and local concentration gradient effects at the interfaces (or concentrating reagents in the stern layer); therefore, the rates were enhanced …”
Section: Resultsmentioning
confidence: 99%
“…Geometric CSMs and CShMs have been successfully applied to a variety of stereochemical problems such as the description of the coordination environement, chirality, and reactivity of chemical compounds . The usefulness of these measures is especially evident when they are applied in conjunction with a statistical analysis to a large set of structural data obtained from a search in databases such as the Cambridge Structural Database .…”
Section: Geometric Csmsmentioning
confidence: 99%